Finite Element Analysis of T-Shaped Concrete-Filled Steel Tubular Short Columns with Stiffening Ribs Under Axial Compression - Xiaosan Yin; Hongliang Yue; Yuzhou Sun; Guoyang Fu; Jimin Li; Md. Mashiur Rahman (Buildings)
A new type of stiffening rib is proposed to improve the mechanical performance of T-shaped concrete-filled steel tubular (CFST) columns. A finite element model was established using the general-purpose commercial software ABAQUS 2022. After verification through comparison with experimental data, the developed finite element model was employed to numerically evaluate the performance of T-shaped CFST short columns with stiffening ribs under axial compression. The results indicated that the new stiffening ribs are capable of significantly reducing the buckling deformation of the steel tube, enhancing the confinement effect of the steel tube on the core concrete, and improving the combined performance of the steel tube and the concrete. The thickness and material strength of the stiffening ribs had a notable impact on the ultimate bearing capacity and ductility of the short column specimens. When the thickness of the stiffening ribs increased from 5 mm to 8 mm, the ultimate bearing capacity correspondingly increased by 10.51% to 31.77%, while the ductility coefficient improved by 6.48% to 17.20%. When the steel strength increased from 262.50 MPa to 345 MPa and 390 MPa, the ultimate bearing capacity correspondingly increased by 17.36%, 19.78%, and 30.50%, and the ductility coefficient improved by 12%, 13.87% and 23.92%. The changes in the specifications and arrangement of the stiffening ribs had no significant effect on the ultimate bearing capacity and ductility of the specimens. The change in angle steel specifications caused variations in ultimate bearing capacity within ±5% and variations in the ductility coefficient within ±10%. Changes in the arrangement caused variations in ultimate bearing capacity within ±1% and variations in the ductility coefficient within ±5%.